Clinico-epidemiological characteristics of men and women with a new diagnosis of chronic obstructive pulmonary disease: a database (SIDIAP) study - Josep Montserrat-Capdevila; Josep Ramon Marsal; Marta Ortega; Maria Teresa Castañ-Abad; Miquel Alsedà; Ferran Barbé; Pere Godoy (BMC Pulmonary Medicine, 2021)
Abstract Background The risk of developing Chronic Obstructive Pulmonary Disease (COPD), the associated comorbidities and response to bronchodilators might differ in men and women. The objective of this study was to determine the prevalence of COPD and the clinic-epidemiological characteristics of primary care patients with COPD according to gender. Methods This is a cross-sectional study using electronic healthcare records Catalonia (Spain), during the 01/01/2012–31/12/2017 period. Patients from the SIDIAP database (System for the Development of Research in Primary Care) were included (5,800,000 patients registered in 279 primary care health centres). Clinic-demographic characteristics, comorbidities and blood tests results were collected for each patient. Adjusted OR (ORa) with logistic regression methods were used to determine variables associated with men and women. Results From an initial sample of 800,899 people, 24,135 (3%) were considered COPD patients, and 22.9%were women. The most common risk factors in women were bronchiectasis (ORa = 20.5, SD = 19.5–21.6), age > 71 years (ORa = 18.8; SD = 17.3–20.5), cor pulmonale (ORa = 5.2; SD = 4.3–6.7) and lung cancer (ORa = 3.6, SD = 3.2–4.0). Men and women presented the same comorbidities, though the strength of association was different for each gender. Conclusions Patients suffering high comorbidity rates. Comorbidities are similar in men and women, although the strength of association varies according to gender. Women are more susceptible to the harmful effects of smoking and present a higher proportion of bronchiectasis and OSAS.